Graphene-doped Ni-Co-B composite material and preparation method thereof
By introducing graphene into the nickel-cobalt bimetal oxide electrode material, graphene-doped Ni-Co-B composite material is prepared, which solves the problem of structure collapse of nickel-cobalt oxide during charging and discharging, and significantly improves the cyclic stability and specific capacitance of the material.
Patent Information
- Application Number
- CN202510047421.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-05-02
AI Technical Summary
The existing nickel-cobalt bimetallic oxide electrode materials collapsed and damaged during charging and discharge, resulting in poor circulation stability and rapid capacity decay.
By combining liquid phase redox reaction and heat treatment under Ar gas protection, graphene-doped Ni-Co-B composite materials are prepared, and graphene is introduced to improve material structure and electrochemical properties.
The cyclic stability and specific capacitance of Ni-Co-B composite materials were significantly improved, and the capacity retention rate of the material reached 100% after 3000 cycles, which was better than the 78.7% of the undoped materials.
Smart Images

Figure CN119920636A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a graphene-doped Ni-Co-B composite material and a preparation method thereof. Background Art
[0002] The development of electrode materials with high specific capacitance, high rate charge and discharge performance and long cycle life is the key to improving the performance of supercapacitors. There are three main types of supercapacitor electrode materials: carbon-based materials, metal (hydride) oxides and conductive polymer materials. Among them, transition metal (hydride) oxides have abundant reserves and their morphology and structure are relatively easy to control, making them a class of highly promising supercapacitor electrode materials. Among the many transition metal oxides, nickel-cobalt bimetallic oxides have very high theoretical specific capacity and have become a hot topic of research. However, since the electronic and ionic conductivity of nickel-cobalt oxides is still poor, their rate charge and discharge performance and cycle stability still need to be improved.
[0003] Studies have found that after doping with heteroatoms such as B, S, N, and P, the conductivity and electrochemical activity of metal oxide materials can be improved to a certain extent, and their electrochemical performance is also improved accordingly. Therefore, heteroatom doping of nickel-cobalt bimetallic oxides is expected to further improve their performance. Zhang Wei et al. synthesized a Ni-Co-B composite material composed of 60-80 nanometer particles. Although the specific surface area is only 27.4 m 2 / g, the specific capacitance reached 1310F / g, and the capacity retention rate at 20A / g relative to 1.5A / g reached 47%, but the cycle stability of the electrode material was poor, and the capacity decayed to 65% after 500 cycles of charge and discharge; ChenRongna et al. prepared a Ni-Co-B composite material containing some Ni(OH)2, which showed very high specific capacitance and rate charge and discharge performance, but slightly poor cycle stability, and the capacity decayed to 94.5% after 1000 cycles; the poor cycle stability can be mainly attributed to the large volume change of the electrode material during the charge and discharge process, which leads to irreversible structural collapse and damage, resulting in capacity decay.
[0004] Since its discovery, graphene has been often used to construct supercapacitor electrode materials with transition metal (hydr) oxides. Its large specific surface area can effectively improve the agglomeration of transition metal oxide particles and increase their utilization rate, thereby increasing the specific capacity of the electrode material. Graphene's excellent conductivity can provide a fast electron transmission channel for the Faraday reaction occurring on the surface of transition metal oxides, improving the material's rapid charge and discharge capabilities. More importantly, graphene can effectively buffer the volume change of the electrode material during the charge and discharge process, protect the electrode material structure, and improve the cycle stability.
[0005] This application combines the rapid redox reaction in the liquid phase with the heat treatment under Ar gas protection to synthesize Ni-Co-B and graphene-doped Ni-Co-B nanocomposites, and studies the effect of graphene introduction on the structure and electrochemical properties of Ni-Co-B electrode materials. The results show that the introduction of graphene can effectively improve the supercapacitor performance of Ni-Co-B, especially its cycle stability, providing a new idea for the development of high-performance transition metal oxide electrode materials. Summary of the invention
[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a graphene-doped Ni-Co-B composite material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a graphene-doped Ni-Co-B composite material comprises the following steps:
[0009] S1, adding NaBH4 to a NaOH solution placed in an ice water bath to obtain a NaBH4 solution;
[0010] S2. At room temperature, NiCl2 and CoCl2 were added to deionized water and graphene oxide (GO) dispersion, stirred for 8-12 min, and then the 1 mol / L NaBH4 solution prepared in step S1 was quickly added, and stirring was continued for 28-32 min. Graphene-doped Ni-Co-B (RNCB) precursor was obtained by vacuum filtration, washing, and freeze drying;
[0011] S3. The RNCB precursor prepared in step S2 is kept at 300° C. for 2 h under an inert atmosphere, and then cooled to room temperature to obtain a graphene-doped Ni-Co-B (RNCB) finished product.
[0012] Preferably, the concentration of the NaOH solution is 0.1 mol / L;
[0013] The concentration of the NaBH4 solution is 1 mol / L.
[0014] Preferably, graphene oxide (GO) is prepared by a modified Hummers method, and then ultrasonically dispersed in deionized water to obtain a 1 g / L graphene oxide dispersion.
[0015] Preferably, the ultrasonic power is 100-500W, and the time is 0.5-3 hours.
[0016] Preferably, the concentrations of NiCl2 and CoCl2 are both 1 mol / L.
[0017] Preferably, the inert atmosphere is argon.
[0018] A graphene-doped Ni-Co-B composite material prepared by adopting a method for preparing a graphene-doped Ni-Co-B composite material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. Amorphous Ni-Co-B (NCB) and graphene-doped Ni-Co-B (RNCB) composites were prepared by chemical reduction method. The specific surface area of RNCB is 3.2 times that of NCB.
[0021] 2. The specific capacity of RNCB at all current densities is higher than that of NCB.
[0022] 3. The electrochemical test results show that the specific capacitance of RNCB at 1A / g reaches 968F / g, and the specific capacitance at 15A / g is still 723F / g, which is better than 817F / g at 1A / g and 660F / g at 15A / g of NCB. More importantly, the introduction of rGO significantly improves its cycle stability. After 3000 cycles, the capacity of RNCB has not decayed, while the retention rate of NCB is only 78.7%.
[0023] 4. The good electrochemical performance of RNCB is mainly attributed to the introduction of graphene, which improves the utilization rate of NCB materials and increases their specific capacitance. In addition, the introduction of graphene can better alleviate the structural collapse and shedding problems of NCB materials during the charging and discharging process, and improve the cycle life of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 XRD spectra of NCB, RNCB and their precursors of the present invention;
[0026] Figure 2 Raman spectra of NCB and RNCB of the present invention;
[0027] Figure 3 It is the XPS spectra of NCB and RNCB elements of the present invention;
[0028] Figure 4 It is the SEM picture of NCB and RNCB of the present invention;
[0029] Figure 5 TEM images, HRTEM images and SAED images of NCB and RNCB of the present invention;
[0030] Figure 6 The nitrogen adsorption-desorption curves and pore size distribution curves of NCB and RNCB of the present invention;
[0031] Figure 7 Graph showing the electrochemical performance of the NCB and RNCB of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] Preparation of 1 mol / L NaBH4 solution: Add 1.9 g NaBH4 to 50 mL 0.1 mol / L NaOH solution placed in an ice-water bath to obtain a 1 mol / L NaBH4 solution.
[0035] Preparation of RNCB: At room temperature, 0.5 mL of 1 mol / L NiCl2 and 1 mL of 1 mol / L CoCl2 were added to 35 mL of deionized water and 15 mL of 1 g / L GO dispersion and stirred for 10 min. Then, 5 mL of the prepared 1 mol / L NaBH4 solution was quickly added and stirred for 30 min. The RNCB precursor was obtained by vacuum filtration, washing and freeze-drying. Finally, it was kept at 300 °C for 2 h under Ar atmosphere and cooled to room temperature to obtain the RNCB finished product, i.e., sample 1.
[0036] Example 2
[0037] Preparation of 1 mol / L NaBH4 solution: Add 19 g NaBH4 to 500 mL 0.1 mol / L NaOH solution placed in an ice-water bath to obtain a 1 mol / L NaBH4 solution.
[0038] Preparation of RNCB: At room temperature, 5 mL of 1 mol / L NiCl2 and 10 mL of 1 mol / L CoCl2 were added to 350 mL of deionized water and 150 mL of 1 g / L GO dispersion, and stirred for 10 min. Then, 50 mL of the prepared 1 mol / L NaBH4 solution was quickly added and stirred for 30 min. The RNCB precursor was obtained by vacuum filtration, washing, and freeze-drying. Finally, it was kept at 300 °C for 2 h under Ar atmosphere and cooled to room temperature to obtain the RNCB finished product, i.e., sample 2.
[0039] Example 3
[0040] Preparation of 1 mol / L NaBH4 solution: Add 190 g NaBH4 into 5000 mL 0.1 mol / L NaOH solution placed in an ice water bath to obtain a 1 mol / L NaBH4 solution.
[0041] Preparation of RNCB: At room temperature, 50 mL of 1 mol / L NiCl2 and 10 mL of 1 mol / L CoCl2 were added to 3500 mL of deionized water and 1500 mL of 1 g / L GO dispersion and stirred for 10 min. Then, 500 mL of the prepared 1 mol / L NaBH4 solution was quickly added and stirred for 30 min. The RNCB precursor was obtained by vacuum filtration, washing and freeze-drying. Finally, it was kept at 300 °C for 2 h under Ar atmosphere and cooled to room temperature to obtain the RNCB finished product, i.e., Sample 3.
[0042] Comparative Example: Preparation of amorphous Ni-Co-B (NCB) composite material
[0043] The difference between this comparative example and Example 1 is that no GO dispersion was added.
[0044] During the preparation of NCB and RNCB, with the addition of sodium borohydride solution, the solution quickly turned black and a large amount of gas escaped. As the reaction proceeded, the gas decreased until it no longer escaped.
[0045] 1.1 Structural characterization of samples
[0046] The crystal structure was analyzed by X-ray diffractometer (XRD, DX-2700, Dandong Haoyuan), and Raman characterization (Raman) was performed on a Raman spectrometer (DXR, Thermo Scientific, USA). The surface morphology and crystal structure were characterized by scanning electron microscopy (SEM, S4800, Hitachi, Japan), transmission electron microscopy (TEM, TECNAI G20, FEI, USA) and selected electron diffraction (SAED) equipped with an energy dispersive spectrometer (EDS). The bonding mode, elemental composition and valence state of sample 1 were analyzed by X-ray photoelectron spectroscopy (XPS, ESCALAB250, Thermo Scientific, USA). The specific surface area and pore structure of sample 1 were characterized by a specific surface area analyzer (BET, QuadraSorb Station 1, Quantachrome, USA).
[0047] 1.2 Electrochemical performance characterization
[0048] Sample 1 was mixed with carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and a certain amount of nitrogen methyl pyrrolidone (NMP) was added. The mixture was sheared and mixed by a high-speed homogenizer. A certain amount of the dispersion was dropped onto a clean piece of nickel foam of about 1 cm × 1 cm, and vacuum dried in a vacuum drying oven at 120 ° C for 12 hours. The electrode ear and another piece of nickel foam were added, and the pressure was pressed to 10 MPa to prepare a working electrode. The loading amount of each electrode active substance was 3.2 mg. The electrochemical properties of sample 1 were characterized by a three-electrode system. The HgO / Hg (1 mol / L NaOH) electrode and the Pt sheet electrode were used as the reference electrode and the counter electrode, respectively, and the electrolyte was 6 mol / L KOH solution. The cyclic voltammetry curve (CV), charge-discharge curve (GCD) and electrochemical impedance spectroscopy (EIS) were measured by an electrochemical workstation (RST 5200F, Zhengzhou Shiruisi), and the cycle performance was tested on a battery test system (CT2001A, Wuhan Lanbo).
[0049] Results and Discussion
[0050] 2.1 XRD and Raman analysis
[0051] XRD spectrum( Figure 1 ) shows that before calcination, there are no obvious peaks in the NCB precursor and the RNCB precursor, indicating their amorphous structure. This may be due to the violent reaction between nickel and cobalt ions and sodium borohydride, which is not conducive to the formation of good crystals. After calcination at 300°C for 2 hours in Ar atmosphere, there are no sharp peaks in the NCB and RNCB spectra. Only NCB has a relatively wide peak at the 45° position, which also shows the amorphous structure of the two. The Raman spectrum of RNCB and the spectrum of NCB ( Figure 2 ) compared to about 1340cm -1 and 1590cm -1 The characteristic D band and G band belonging to carbon materials appear obviously at the position, indicating that rGO is well embedded in the RNCB composite material.
[0052] 2.2 XPS analysis
[0053] The electronic structure and chemical composition of NCB and RNCB were analyzed using XPS technology. Figure 3 As shown in Figure 2, the NCB composite material is mainly composed of four elements: Ni, Co, O and B, while the RNCB is composed of five elements: Ni, Co, O, B and C. Ni 2p, Co 2p and B1s spectra of NCB and RNCB composite materials ( Figure 3 a, b, c, e, and f) are relatively close, among which the peaks at about 874.8 eV and 856.9 eV in the Ni 2p spectrum are respectively close to the characteristic Ni 2p 1 / 2 and Ni 2p 3 / 2 The binding energies are consistent, and the peaks at about 797.5 eV and 781.6 eV in the Co 2p spectrum correspond to the characteristic Co 2p 1 / 2 and Co 2p 3 / 2 The binding energy is consistent. In the B 1s spectrum, there is only a strong peak at about 192.1eV, corresponding to the oxidized B, indicating that the B element has been compounded into the NCB and RNCB materials. Figure 3 d, 3h), a peak at 531.5 eV appeared, corresponding to the O-Ni(Co) bond, indicating that the composite material contains nickel-cobalt oxides. In addition, there is an additional peak at 529.8 eV in the O1s spectrum of RNCB, corresponding to the CO-Ni(Co) valence bond. Figure 3 i) It can be resolved into four peaks located at 284.6, 285.5, 286.5 and 289.3 eV, corresponding to C=C, COH, COC and C(O)-O bonds, respectively, further illustrating the successful introduction of rGO.
[0054] 2.3 Micromorphology analysis
[0055] SEM photos ( Figure 4 ) shows that NCB is mainly composed of particles of tens of nanometers, and some nano-sheet structures can also be observed, which may be the oxides of nickel and cobalt. With the addition of reduced graphene, the particles of RNCB increase to between one hundred and several hundred nanometers. From the high-magnification SEM photos, it can be seen that after adding graphene, nickel cobalt boride wraps the reduced graphene in sheets. TEM photos ( Figure 5a, 5d) show that NCB is mainly composed of particles with a size of tens of nanometers accompanied by a small amount of lamellar structures. HRTEM images ( Figure 5 b, 5e) show that the nanoparticles are amorphous structures with short-range order and long-range disorder. The SAED spectrum ( Figure 5 c, 5f) further proves its amorphous structure, which is consistent with the XRD results. The TEM photo of RNCB shows that the material is formed by nickel-cobalt boride particles coating the graphene surface, and it is difficult to directly observe the exposed graphene. The results of HRTEM and SAED also prove its amorphous structure. In order to further obtain the elemental composition of sample 1, EDS analysis was performed on it. The results showed that the atomic proportions of Ni, Co, B, and O elements in NCB were 20.6%, 38.0%, 5.9%, and 35.5%, respectively, and the atomic proportions of Ni, Co, B, C, and O elements in RNCB were 15.3%, 31.3%, 4.2%, 7.1%, and 42.1%, respectively. The content of nickel and cobalt elements in NCB or RNCB samples is close to 1:2, which is close to the raw material ratio. In addition, the content of B element in RNCB is slightly lower than that in NCB, which may be due to the consumption of part of sodium borohydride by the reduction of GO. From the content of O element, it can be seen that both NCB and RNCB contain nickel and cobalt oxides.
[0056] Figure 6 a is the nitrogen adsorption-desorption curve of NCB and RNCB. Both of them have obvious hysteresis loops, indicating that there are more mesopores. There is no obvious saturated adsorption platform, indicating that there are multiple pores. This is consistent with the pore size distribution curve ( Figure 6 According to the BJH theory and DFT theory, the average pore diameters of NCB and RNCB are 3.128 nm and 3.733 nm, respectively, the total pore volumes are 0.3086 cc / g and 0.4012 cc / g, respectively, and the specific surface area is 49.3 m 2 / g and 209.5m 2 / g, it can be seen that after adding graphene, the average pore size and pore volume of the samples are slightly increased, but the specific surface area increases by 3.2 times.
[0057] 2.4 Electrochemical performance analysis
[0058] Figure 7a, b are the CV curves of NCB and RNCB electrode materials at various scanning rates. It can be seen that both have a pair of obvious redox peaks, indicating their pseudocapacitive storage mechanism. With the increase of the scanning rate, the shape of the CV curve does not change much, but the redox peak potential difference increases significantly, indicating that the redox reversibility of the electrode is related to the rate-controlled process kinetics. Comparing the CV curves of NCB and RNCB, it can be seen that at the same scanning rate, the area of the CV curve of RNCB is larger than that of the CV curve of NCB, indicating that the RNCB material has higher electrochemical activity and material utilization. In order to further obtain the specific capacitance of the material, a constant current charge and discharge test was carried out on it. The results are shown in the figure. Figure 7 c, d, e, and f. It can be seen that a pair of charge and discharge platforms are consistent with a pair of redox peaks in the CV curve results. According to the charge and discharge curves, the specific capacitance of the NCB electrode at 0.5, 1, 2, 4, 6, 10, and 15 A / g is calculated to be 817, 780, 770, 768, 732, 700, and 660 F / g, respectively, showing very excellent rate charge and discharge performance. This is mainly due to the small particle size of the NCB material, which leads to faster ion diffusion. The specific capacitance of the RNCB electrode at 0.5, 1, 2, 4, 6, and 10 A / g is 968, 948, 920, 888, 840, 780, and 723 F / g, respectively, which also has excellent rate charge and discharge performance, and the specific capacitance at each current density is higher than that of NCB. This is mainly due to the introduction of graphene materials, which increases the specific surface area and improves the utilization rate of pseudocapacitive materials. From the specific capacitance rate retention of the electrode material, it can be seen that the specific capacitance of the NCB electrode material at 15A / g is 80.8% at 0.5A / g, which is higher than 74.7% of RNCB, showing the excellent rate charge and discharge performance of the NCB material itself. The EIS spectrum can further study the kinetic characteristics of the electrode interface reaction process in the electrochemical system. Figure 7 gIt can be seen that both the small semicircle in the high-frequency region and the slope in the low-frequency region are relatively close, indicating that the charge transfer resistance between the electrolyte interface and the electrode is small and the ion conductivity is high, which further explains the excellent rate charge and discharge performance of the electrode.
[0059] Figure 7h is the cycle life graph of the NCB and RNCB composite material. It can be seen that the specific capacitance of NCB increases slightly at the beginning due to the continuous activation of the electrode, and as the number of cycles increases, the specific capacitance gradually decreases. After 3000 cycles, the capacity retention rate is 78.7%. The specific capacitance of the RNCB electrode gradually increases in the first few hundred cycles, and then remains basically stable. After 3000 cycles, the specific capacitance retention rate is 100%, showing very excellent cycle stability. This may be due to the introduction of graphene. On the one hand, as a substrate, it can load the NCB material well, making it not easy to fall off during the charge and discharge process. On the other hand, graphene can well buffer the volume change of the NCB material during the charge and discharge process, preventing its structural collapse, thereby improving the cycle life of the material.
[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a graphene-doped Ni-Co-B composite material, characterized in that: The following steps are involved: S1, adding NaBH4 to a NaOH solution placed in an ice water bath to obtain a NaBH4 solution; S2. At room temperature, NiCl2 and CoCl2 are added to deionized water and graphene oxide dispersion, stirred for 8-12 minutes, and then the 1 mol / L NaBH4 solution prepared in step S1 is quickly added, and stirring is continued for 28-32 minutes. The graphene-doped Ni-Co-B precursor is obtained by vacuum filtration, washing, and freeze drying; S3. The RNCB precursor prepared in step S2 is kept at 300° C. for 2 h under an inert atmosphere, and then cooled to room temperature to obtain a graphene-doped Ni-Co-B finished product.
2. The method for preparing a graphene-doped Ni-Co-B composite material according to claim 1, characterized in that: The concentration of the NaOH solution is 0.1 mol / L; The concentration of the NaBH4 solution is 1 mol / L.
3. The method for preparing a graphene-doped Ni-Co-B composite material according to claim 1, characterized in that: Graphene oxide was prepared by a modified Hummers method and then ultrasonically dispersed in deionized water to obtain a 1 g / L graphene oxide dispersion.
4. The method for preparing a graphene-doped Ni-Co-B composite material according to claim 3, characterized in that: The ultrasonic power is 100-500W, and the time is 0.5-3 hours.
5. The method for preparing a graphene-doped Ni-Co-B composite material according to claim 1, characterized in that: The concentrations of NiCl2 and CoCl2 are both 1 mol / L.
6. The method for preparing a graphene-doped Ni-Co-B composite material according to claim 1, characterized in that: The inert atmosphere is argon.
7. A graphene-doped Ni-Co-B composite material prepared by the method for preparing a graphene-doped Ni-Co-B composite material according to any one of claims 1 to 6.